The Relationship Between Teacher’s Job Satisfaction with Teacher’s Job Performance at Primary Schools - Siti Norziah Ismail; Mahfuzah Meran (Research in Management of Technology and Business, 2021)
Job satisfaction is closely related to an individual’s job performance. When a person is satisfied with the work that they do, they will be motivated to do their work sincerely and intensely. Hence, it will indirectly improve their job performance. The purpose of this study was to identify the relationship between job satisfaction and job performance among at Kem Terendak, Malacca. This study also wants to determine the most influential factor in job satisfaction among primary school teachers at Kem Terendak. To achieve the goal, a questionnaire was designed and was administered to a sample research consisted of 58 teachers randomly selected from two primary schools in the Kem Terendak. Statistical Package for Social Sciences (SPSS) software was used in this study to analyses data. For descriptive analysis, responses were evaluated and analysed in terms of mean, percentage and standard deviation. To compare and test hypotheses, inference analyses such as Spearman’s Correlation and Cronbach’s Alpha were used. Significantly from this study may help primary school teachers in the Kem Terendak area to improve the quality of teaching methods to be delivered to primary school students and at the same time can enhance the performance of teachers. In addition, the principal needs to supervisory that will help them understand the wants and needs of all schools whether the staff, non-teacher staff and students as well as the local community in leading the school to excellence.